Determinants of Sexual and Reproductive Health among Brazilian youth (aged 18 to 29 years old) - Miguel Barbosa Fontes; Rdrigo Campos Crivelaro; Alice Margini Scartezini; David Duarte Lima; Alexandre de Araújo Garcia; Rafael Tsuyoshi Fujioka (Acta Scientiarum. Health Sciences, 2016)
This study assessed the main determinants of sexual and reproductive health of Brazilian youth. It was approved by the Ethics Committee of the Medicine Faculty of the University of Brasília, and it received support from Paho and Brazilian Ministry of Health. 1.208 youngsters (18 to 29 years old) in 15 states and Federal District were interviewed at their residences, during the second semester of 2011. Margin of error, adjusted regional and nationally, was 2.8% (CI: 95%), regarding the assessed sample. A KAP scale (knowledge, attitudes, and practices) with 17 questions (-17 to +17 points) was generated. A questionnaire was pre-tested for consistency and validity analysis was performed. KAP scale was used as dependent variable in adjusted linear regression models. Mean KAP score was 5.65 points. Gaps in KAP were: 70% of the youth do not know when the fertility period of a woman is. 42% of youth do not recognize condoms as a method to prevent unwanted pregnancy and STDs. The main factors associated to explaining variances in KAP are gender, education, religion, access to health services, having had sexual intercourse in the last 12 months, and having friends as the main personal reference (p < 0.05). Youngsters with higher education, women, non-Protestant, who claim to know where to find health services have better KAP level of reproductive health. Studies are necessary to support public policies that increase the KAP levels in sexual and reproductive health of the most vulnerable groups, such as the segment comprising low education, men and Protestants.